The Place of Personification in the Semantic Structure of Metaphor (Based on the French Language) - Mamadaliyev A; Khamrakulova F (Periodica Journal, 2022)
This article discusses the semantic basis of personification of its identification in the semantic structure of the word and its use in the flow of speech. And also its differences from the phenomena close to it are indicated as "animation" "animalization". And we have to come to the conclusion that "personification" is giving actions properties and signs of an anthroponym to nonanthroponyms on the basis of a common seven.
Keywords: general seme; anthroponym; two-isotopy; multidimensional